ALOPECIA X IN GERMAN SPITZ RESPONSIVE TO ORCHIECTOMY ASSOCIATED WITH THE USE OF MELATONIN: CASE REPORT - Dossena, Ana Paula; Luvison, Nicole Amoêdo; Zardin, Ketlin Milena; Barros, Camille Moreira Bergamo; Saraiva, Gabriela Victoria Araújo; Medeiros, Dreyd Rodrigues; Teixeira, Barbara Fernandes Werneck; da Silva, Édios Meurer Lana; Martins, Carolina Aires; Cipriano, Luanda Ferreira (Seven Editora, 2025)
Alopecia X is a dermatological disorder that mainly affects Nordic breed dogs. Its cause is not completely clear. Alopecia X is characterized by its non-inflammatory aspect, being similar to endocrine-based dermatopathies. The main lesions are progressive hair loss in the affected areas, being less pronounced on the head and distal extremities of the limbs in more advanced cases. This study aims to report a case of alopecia X in a male, uncastrated German Spitz dog. At the first visit, an initial case of bilateral symmetrical alopecia was observed on the caudal side of the thighs and perineum, without pruritus, macroscopic signs of inflammation and clinical signs of systemic diseases. The patient underwent additional tests (including trichogram, skin scraping, direct ectoparasite screening and blood profile) in which parasitic and systemic diseases were ruled out. Based on clinical aspects, racial predisposition and exclusion of systemic causes, the diagnosis of alopecia X was considered. The treatment of choice was orchiectomy associated with the use of Melatonin, initially for 3 months. After 90 days of treatment, partial regrowth of the alopecic areas was observed, as well as a reduction in the area without hair, with return of primary and secondary hairs in the affected region. It is concluded in this case that the choice of orchiectomy associated with the use of melatonin was effective in improving the dermatological condition, and can be used as an ally. DOI: https://doi.org/10.56238/sevened2024.037-182